PENGARUH LABA SAHAM, LIKUIDITAS, DAN LEVERAGE TERHADAP KEBIJAKAN DIVIDEN DENGAN SIZE SEBAGAI VARIABEL MODERASI - Fadli Ali Taslim; Tria Irma Afrianti Muhlis (Jurnal Manajemen Sinergi, 2016)
This research aims to test the impact of share earnings, liquidity, and leverage toward dividend policy with size as moderating variable. This research’s population is manufacturing companies listed in Indonesia Stock Exchange (BEI). Samples are chosen with purposive sampling method and resulted in 21 samples with time span of 5 years that is from 2010 to 2014. Research results showed that share earnings (EPS) has positive impact towards dividend policy (DPR), liquidity (CR) has negative impact towards dividend policy, and leverage (DER) has positive impact towards dividend policy (DPR). Whereas company size (SIZE) as moderating variable, is capable to moderate and strengthen the impact of share earnings (EPS) towards dividend policy and size (SIZE) doesn’t become a moderating variable between the impact of liquidity (CR) towards dividend policy (DPR). Meanwhile, size (SIZE) is capable to be the moderating variable and strengthening the impact of leverage (DER) towards dividend policy (DPR).